IMPLEMENTASI KEBIJAKAN PENGADAAN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) PADA GURU HONORER DI KOTA SUKABUMI TAHUN 2021 - Linda Zakiah; Andi Mulyadi; Dine Meigawati (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
This study aims to find out how the implementation is implemented and find out what are the obstacles in the policy of procuring Government Employees with Work Agreements (PPPK) for honorary teachers in Sukabumi City. In order to approach this problem, the theoretical references of Donald S. Van Metter & Carl E. Van Horn are used, using 6 variables including a) Executor's size and objectives, b) Resources, c) Relationships between organizations, d) Characteristics of implementing organizations, e ) Social, political and economic conditions, f) Disposition of the executors. The data collected through observation, interviews, and documentation were analyzed qualitatively. The results of this study indicate that the implementation in Sukabumi City is running effectively and has no significant obstacles, the implementation of PPPK procurement policies in Sukabumi City has involved various parties who pay attention to the relevant parties, optimizing existing resources, maintaining inter-organizational relations, prioritizing the character of implementing organizations, conditions social, political, and economic, as well as maintaining the disposition of the executors.